Performance of the Rheumatoid Arthritis Impact of Disease (RAID) score in relation to other patient-reported outcomes in a register of patients with rheumatoid arthritis. Issue 6 (6th March 2011) - Heiberg, Turid; Austad, Cathrine; Kvien, Tore K; Uhlig, Till
Abstract : Objective: Delegates at the Outcome Measures in Rheumatology (OMERACT) 10 conference (Borneo, 4–8 May 2010) questioned how the new seven-domain Rheumatoid Arthritis Impact of Disease (RAID) score performs as a global measure. Score distributions and associations between the RAID score and patient-reported outcomes (PROs) and demographic variables were examined in a large sample of rheumatoid arthritis (RA) patients. Methods: 1086 patients in the Oslo RA Register responded to a postal survey with commonly used PROs. Bivariate associations between the RAID score and other measures are reported as Pearson correlation coefficients. Results: The mean RAID was 3.37±2.17. The distribution of the RAID score showed a slight floor effect: 17.5% had a score between 0 and 1, and 14.4% between 1 and 2, whereas only 1.0% and 0.3% had scores between 8 and 9, and 9 and 10, respectively. Correlations between the RAID score and the patient global assessment, Rheumatoid Arthritis Disease Activity Index, Short-Form (SF)-6D and EQ-5D were 0.82, 0.82, −0.77 and −0.73, respectively. Strong correlation was also seen between RAID and pain, the domain with highest weight, whereas correlations to measures of other RAID domains were moderate. The RAID score was higher in women than men (3.49 vs 2.95, p=0.001). Conclusion: The RAID score was correlated more strongly to other global measures than to PROs, reflecting single health domains.